Pengaruh Kombinasi Ekstrak Daun Kelor Dan Sari Kurma Terhadap Peningkatan Kadar Hemoglobin Remaja Putri - Hindratni, Findy; Sari, Septi Indah Permata; Gizta, Aura Bella; Sari, Septi; Gizta, Aura (JURNAL PROTEKSI KESEHATAN, 2025)
Low hemoglobin levels can cause decreased immunity, healthiness, and thinking dexterity which leads to reducing learning achievement and productivity of adolescent girls. There were 21,010 women of reproductive age in Indonesia that suffering from low hemoglobin levels in 2019. The purpose of this study was to determine the effect of the combination of moringa leaf extract and date palm extract on increasing hemoglobin levels of adolescent girls at MAN Tanjungpinang. This research was conducted in January – April 2022, with samples of 15 adolescent girls. Samples were given intervention with 2x500 mg moringa leaf extract and 2x15 ml date palm extract for 12 days. Data analyzed using Wilcoxon test with 5% α. The results showed that the average hemoglobin level before intervention was 14,147 g/dL, and the average hemoglobin level after intervention was 15,960 g/dL. There was an effect of the combination of moringa leaf extract and date palm extract on increasing hemoglobin levels of adolescent girls at MAN Tanjungpinang (p = 0,001).